STRATEGI PENGEMBANGAN USAHA TERNAK AYAM PEDAGING (STUDI KASUS PADA USAHA PATRIOT DI DESA MASARI KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG PROVINSI SULAWESI TENGAH) - Tauhid, Moh.; Hadayani, Hadayani; Tangkesalu, Dance (AGROTEKBIS, 2019)
Broiler business in Patriot business still applies traditional farming system with such weaknesses as relatively simple production equipment, relatively high mortality rate and limited human resources.  Data collected was analyzed using SWOT Analysis. The IFAS value was 3.22, with the strength value was 2.27 and the weakness value was 0.95. This shows that the strength factor in the "Patriot" business is greater than the weakness factor.  The EFAS value was 3.54, with the opportunity value was 1.60, and the threat value was 1.94.  Based on the internal and external factors, the total score of  the strength and the weakness factors positioned at X axis was equal to 1.32, while that of the opportunity and the threat positioned at Y axis was equal to 0.34. The appropriate development strategy for Patriot business is ST strategy. Therefore, the best strategy for the Patriot business development is Strength-Threat strategy, the strategy of using strength to overcome the threats.